Examining the Impact of Early Marriage Hadith on Marriage Laws in Indonesia - Luthfi, A Hashfi; Hamdani, Nabhan; Ruhiat, Andri; Adlimah, Annilta Manzilah; Solahuddin, Ahmad (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2023)
This research aims to investigate the impact of the hadith narrating the marriage between Prophet Muhammad and Aishah on early marriage laws in Indonesia. The hadith has been a subject of debate regarding its influence on the prevalence and acceptance of early marriage practices. Through a hermeneutics analysis within the Indonesian context, this study examines the interpretations and implications of the hadith, exploring how it has shaped societal attitudes and influenced the formulation of early marriage laws. The research argues that the marriage between the Prophet and Aishah was a “product of time”, rather than an inherent Islamic principle. It posits that Islamic principles can be contextualized across space and time, while product of time are influenced by specific values and circumstances. The study contends that the underlying Islamic principle behind marriage is to enhance the welfare and well-being of women in various aspects of life. The Prophet aimed to improve the status of women by emphasizing the institution of marriage as a means of protection. In contrast, early marriage undermines women’s opportunities for education and independent living. By comparing these perspectives, the study highlights that marriage practices are influenced by historical contexts, while the true Islamic principle seeks to elevate and empower women in social, economic, and educational spheres. The findings of this research contribute to a nuanced understanding of the relationship between religious teachings, cultural practices, and legal frameworks surrounding early marriage in Indonesia.